Humour to learn Mathematics: mathematical tasks to laugh and learn - Menezes, Luís (2021)
Good mood and wellbeing make work and learning much easier. And this is what humour is really all about, to make people feel well and to make them laugh. Humour will minimise stressful situations and facilitate communication. Among the different forms of humour, graphic humour, based on comic strips and cartoons, is constantly present in magazines, newspapers and on the internet. In the HUMAT: Humour in Mathematics teaching project, we have created a set of mathematical tasks based on different graphic humour situations created by different authors that are available on the internet and in magazines and focus on several mathematical contents which are to be taught over the different school years. This book is therefore made for students and its aim is to support the learning of Mathematics, both in the classroom and outside the classroom, always relying on humour and good mood.